Hypervětvené polymery - Hobzová, Radka; Peter, Jakub; Sysel, Petr (Chemické listy, 2008)
Over the recent decades, hyperbranched polymers have received much attention in both academic and industrial sphere. Due to their highly branched structure and multifunctionality, hyperbranched polymers exhibit unique chemical and physical properties. Many hyperbranched polymers have been prepared by one-step polymerization. The polymerizations can be divided into three categories: step-growth polycondensation of ABx monomers, selfcondensative vinyl polymerization of AB* monomers and branching ring-opening polymerization of hypothetical ABx monomers. This review highlights some examples of synthesis of the most important hyperbranched polymers. Special attention is paid to step-growth polycondensation of ABx-type monomers and to polycondensation of A2 and B3 monomers. Some properties of hyperbranched polymers and their potential applications are also described.
Keywords: polymery; financování organizované; vztahy mezi strukturou a aktivitou; Financing, Organized; Structure-Activity Relationship; Polymers